Control of a cart-ball system [compact disc] : comparison between model based and fuzzy logic controllers - 403416 Mohd. Shakir Md. Saat (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2006